Buyer power in international markets - Horst Raff; Nicolas Schmitt (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper investigates the implications for international markets of the existence of retailers/wholesalers with market power. Two main results are shown. First, in the presence of buyer power trade liberalization may lead to retail market concentration. Due to this concentration retail prices may be higher and welfare may be lower in free trade than in autarky, thus reversing the standard effects of trade liberalization. Second, the pro-competitive effects of trade liberalization are weaker under buyer power than under seller power.
Keywords: F12; F15; L13; 330; buyer power; retailing; international trade; Einzelhandel; Nachfragemacht; Außenhandelsliberalisierung; Internationaler Wettbewerb; Handel; Wirtschaftskonzentration; Wohlfahrtseffekt; Theorie